Pengaruh Work-Life Balance, Lingkungan Kerja dan Efisiensi Kerja terhadap Kepuasan Kinerja Karyawan Sadara Resort - I Ketut Yoshi; Ketut Elly Sutrisni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee job satisfaction is often shaped by the balance between personal and professional demands, the quality of the work environment, and the efficiency with which daily tasks are completed. This study examines how work-life balance, work environment, and work efficiency influence job satisfaction among employees of Sadara Resort. A quantitative approach was applied using a saturated sampling technique, involving all 106 active employees. Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS version 25. The findings reveal that work-life balance shows a positive yet statistically insignificant relationship with job satisfaction, indicating that balance alone does not strongly determine employees’ attitudes toward their work. In contrast, both work environment and work efficiency demonstrate positive and significant effects on job satisfaction. Together, the three variables contribute 64.6% to the overall model. These results suggest that improving physical and organizational work conditions, along with enhancing operational efficiency, plays a more prominent role in strengthening job satisfaction within the hospitality sector, particularly in resort-based workplaces.